2020
DOI: 10.1038/s41398-020-00885-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute oxytocin effects in inferring others’ beliefs and social emotions in people at clinical high risk for psychosis

Abstract: Social deficits are key hallmarks of the Clinical High Risk for Psychosis (CHR-P) state and of established psychotic disorders, and contribute to impaired social functioning, indicating a potential target for interventions. However, current treatments do not significantly ameliorate social impairments in CHR-P individuals. Given its critical role in social behaviour and cognition, the oxytocinergic (OT) system is a promising target for novel interventions in CHR-P subjects. In a double-blind, placebo-controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Schmidt et al, 2020), which agrees with our ndings. Furthermore, additional ROI analysis showed activation changes in overlapping region in the left visual cortex (including occipital fusiform gyrus).…”
supporting
confidence: 93%
“…Schmidt et al, 2020), which agrees with our ndings. Furthermore, additional ROI analysis showed activation changes in overlapping region in the left visual cortex (including occipital fusiform gyrus).…”
supporting
confidence: 93%
“…These include anxiolytic effects (36), modulation of social and emotional cognition (3740), hypothalamic-pituitary-adrenal axis regulation (36) and parasympathetic modulation of the heart rhythm (41). In our previous CHR-P work, we demonstrated that oxytocin modulates frontal activation during mentalising (42), anterior cingulate neurochemistry (43) and resting cerebral blood flow in the hippocampus among numerous other regions (44). Independent evidence further suggests that oxytocin modulates connectivity within resting-state networks in healthy volunteers (45,46) and ‘normalises’ aberrant connectivity in several clinical populations, including patients with social anxiety (47), post-traumatic stress disorder (48) and autism (49).…”
Section: Introductionmentioning
confidence: 94%
“…Using a more lenient threshold, we observed increased activation in temporal to occipital regions at Time 2 in the PT group compared with the nonPT group. Other neuroimaging studies using RMET produced similar results(Adams et al, 2010;Castelli et al, 2010;Schmidt et al, 2020). Since the fusiform gyrus is involved in the perception of emotions in facial expressions(Haxby et al, 2002;Mier et al, 2010), the changes in brain activity in the PT group might re ect their increased sensitivity to the other's mental states.Altogether, our ndings suggest that PT interventions in mothers provide them with a better understanding of their children, helping to create a more nurturing environment, and reducing parenting stress, subsequently improving activation in the fusiform gyrus during socioemotional processing.…”
mentioning
confidence: 54%